A Review of Exclusive Breastfeeding Practices Among Lactating Mothers in Nigeria: Cultural Beliefs, Perceptions, and Attitudes - Funke Florence Popoola (INTERNATIONAL JOURNAL OF HEALTH AND PHARMACEUTICAL RESEARCH, 2026)
Background: Exclusive breastfeeding (EBF) is defined as feeding the infant using only breast milk without other food or beverages, including water, within a duration of 6 months since it is enough nutrition that is needed to enable the optimal growth and development of infants during their first 6 months. Objective: This study aims to identify cultural beliefs, perceptions and attitudes of mothers towards exclusive breastfeeding in Nigeria. Findings: In spite of the general awareness of the huge benefits of EBF practice, some gaps in practice were identified in studies. It was reported that 72.2% of the mothers were aware of EBF, and 27.8% practised it, with many of them being unaware of its significance, among female medical practitioner, it was revealed that 95.1% were generally aware of the concept of EBF, but only 52.1% had the ability to identify what it meant. At the core of these shortcomings in the EBF practice, cultural aspects emerge as the key obstacles to EBF in most cultures, and Nigeria is no exception. Conclusion: The findings show that the prevalence of EBF differs widely across economies globally, with the widespread low rates in low- and middle-income countries being influenced by the scarcity of resources and cultural practices, and the alarming trend of rising inpatient and outpatient rates in the last decades. Factors such as individual maternal factors, institutional factors, and cultural and family factors, tends to pressure providers into unjustified early cessation of EBF.